Regulation of hepatic Sirt1 expression and lipid metabolism through TNF receptor signaling - Hines, Ian N.; Stafford, Samuel B.; Bradford, Blair U.; Wheeler, Michael D. (Frontiers in Immunology, 2025)
The production of tumor necrosis factor -alpha (TNFα) has been associated with fatty liver disease (i.e, hepatosteatosis) for many years. In fact, cytokine production has been thought of as a consequence of hepatic lipid accumulation which then becomes a critical factor in the development of chronic liver pathologies as well as in the pathogenesis of insulin resistance. The purpose of this study was to test the hypothesis that TNFα directly regulated lipid metabolism in liver. Wild type mice and mice lacking the receptor for TNFα (TNFR1-/-) were fed control diet or a choline-deficient diet. In addition to pro-inflammatory response, choline-deficient diet increased hepatic lipid accumulation and liver injury, serum triglyceride and insulin levels, as well as increased fasting glucose levels in wildtype mice but to a significantly lesser extent in TNFR1-/- mice. Liver perfusion and metabolic cage studies revealed that TNFR1-/- mice exhibited higher rates of lipid oxidation than wildtype mice. Importantly, TNFR1-/- mice have elevated hepatic expression of metabolic and circadian rhythm regulator SIRT1 in comparison to wild type mice. In isolated hepatocytes, TNF suppressed sirt1 expression while inducing expression of DBC1, a known inhibitor of sirt1 function and expression. These data suggest that TNFα and possibly other innate immune factors play a critical role in the development of hepatosteatosis and the onset of metabolic syndrome. This data also suggests an interplay among innate immunity, hepatic metabolism, and circadian rhythm in the pathogenesis of metabolic syndrome.